Communication consultants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A multi-media group of experienced consultants has been formed by the Danish Broadcasting Corporation. Called DaniCom/Danish Development Communication Consultants, the group is a not-forprofit consulting service specializing in communication and...